A Piyyut for Hoshana Rabbah. Issue 2 (1st September 2020) - Ferreira, Iris
Abstract: A Piyyut for Hoshana Rabbah presents a modern piyyut designed for the last day of the Sukkoth festival. It focuses on the ushpizin that we invited under the sukkah during the festival, presenting not only the male ushpizin mentioned in the Zohar, but also female ones, following the list given in the Machzor Forms of Prayer for Jewish Worship: II Prayers for the Pilgrim Festivals . The goal of this piyyut is to value the biblical characters invited as ushpizin during Sukkoth and their specific destiny in the context of the festival, as well as the progressive value of gender equality.